2016
DOI: 10.1007/s13313-016-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of root disease on white clover growth in New Zealand dairy pastures

Abstract: The cost to clover growth of soil-borne root disease was measured in ten New Zealand dairy pasture soils. The average increase clover growth (weight) after soil pasteurisation was 28.5 %, but ranged from a 64 % increase (Whataroa soil) to a decrease of 11.9 % (Ruakura soil). The economic cost of reduced clover growth was determined using the Farmax Dairy Pro decision support system. In Southland and Canterbury, clover root disease was estimated to cost $750 and $715 ha −1 year −1 respectively, and in the Waika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…In these instances, the net effect of deleterious microflora outweigh the importance of beneficial symbionts in these soils. Recent surveys of pathogenic microorganisms and nematodes in New Zealand pastures have revealed surprisingly large impacts of disease on white clover growth [ 32 , 33 ]. The inoculation of soils harbouring these pathogen-enriched communities into clover growth assays can result in poor outcomes for clover seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, the net effect of deleterious microflora outweigh the importance of beneficial symbionts in these soils. Recent surveys of pathogenic microorganisms and nematodes in New Zealand pastures have revealed surprisingly large impacts of disease on white clover growth [ 32 , 33 ]. The inoculation of soils harbouring these pathogen-enriched communities into clover growth assays can result in poor outcomes for clover seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Management of the soil microbial community towards inducing or enhancing disease suppression presents an emerging, and potentially more enduring, approach to disease control in agricultural systems [ 11 ]. Managing or ‘engineering’ the soil microbiome in this way may prove to be particularly important in pastoral grasslands where the control of diverse pathogens is complicated by multi-plant-multi-pathogen interactions [ 2 , 12 ]. To exploit the natural processes that lead to enhanced disease suppression in pastures, and to support farmers in managing pastoral systems towards a more suppressive state, it is important to develop understanding of the occurrence of suppressive microbiota in the field and how these vary spatially, temporally, and with farm management practices.…”
Section: Introductionmentioning
confidence: 99%
“…There are likely a range of reasons for this difference between studies including temporal (the soils were sampled in different years), spatial (diseases, for instance, can be patchily distributed) and the severity of the treatment imposed. In the current study virtually all microbes were eliminated while the Wakelin et al (2016) method was less severe and may have retained some beneficial microbes which then minimized the negative effects of the sterilization treatment. Root length in all soils were greater in Experiment 2 than Experiment 1, with many root systems reaching the bounds of the pot depth (120 mm).…”
Section: Discussionmentioning
confidence: 69%
“…Skipp and Christensen (1983) recorded the incidence of potential root-rotting fungi on white clover roots during a survey of New Zealand pastures and found that Codinea fertilis predominated in root pieces from two soils in Northland (close to soil 1 in the current study) and that Bimuria novae-zelandiae predominated in soils of Southland (close to the current soil 10). Wakelin et al (2016) found a significant negative association between a Pythium clade and T. repens shoot growth. Whether, these are the causative agents of the root rotting observed in the current study will be clarified by the next generation sequencing results to be carried out on white clover endosphere samples which will be reported in a future paper.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation